2015
DOI: 10.1371/journal.pone.0123220
|View full text |Cite
|
Sign up to set email alerts
|

Sharing the Space: Distribution, Habitat Segregation and Delimitation of a New Sympatric Area of Subterranean Rodents

Abstract: Subterranean rodents of the genus Ctenomys usually present an allopatric or parapatric distribution. Currently, two cases of sympatry have been recognized for the genus in the coastal dunes of southern Argentina and southern Brazil. In this context, they are ideal models to test hypotheses about the factors that delimit the patterns of space use and to understand interspecific interactions in small mammals. We investigated the vegetation structure, plant biomass and soil hardness selected by two species of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…In addition to their morphological similarity, they share the same chromosomal number (2n = 47-48), with the same chromosome G-band pattern among five species (C. flamarioni, C. talarum, C. mendocinus, C. australis and C. porteousi) and have an asymmetric, simple type of sperm with two tails 19,[23][24][25] . C. flamarioni and C. minutus share one of the two sympatric zones described for the genus 26,27 , and in this region, we have information that they can generate hybrids. The common ancestor of torquatus and mendocinus was estimated to have arisen approximately 1.4 million years ago 28 .…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In addition to their morphological similarity, they share the same chromosomal number (2n = 47-48), with the same chromosome G-band pattern among five species (C. flamarioni, C. talarum, C. mendocinus, C. australis and C. porteousi) and have an asymmetric, simple type of sperm with two tails 19,[23][24][25] . C. flamarioni and C. minutus share one of the two sympatric zones described for the genus 26,27 , and in this region, we have information that they can generate hybrids. The common ancestor of torquatus and mendocinus was estimated to have arisen approximately 1.4 million years ago 28 .…”
mentioning
confidence: 76%
“…The results of our work demonstrate unequivocally that, in some cases, species that present extensive chromosome organization, phenotype, evolutionary history, sperm morphology and genetics differences, which are usually associated with reproductive isolation, can generate natural hybrids. Furthermore, a series of findings in the field of ecology demonstrated that these two species present modifications during the occupation of microhabitats 27 and morphological character displacement when in sympatry 48 , revealing that species are capable of recognizing individuals of another species and presenting ecological responses due to competition and yet they come into contact during the reproductive period and produce hybrids. Mitochondrial DNA analyses placed hybrid individuals within both species, thus providing evidence of bidirectional gene flow because females may belong to either species; furthermore, microsatellite analysis revealed that the genetic makeup of the hybrid population was the result of admixture between the two parental species.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…This pattern is likely due to the different characteristics of each environment. Environments with lower bulk density (such as sand dunes) have less biomass than higher density soils (sand fields), as soil density is positively related to the amount of biomass available (food source) (Malizia, Vassallo & Busch, ; Cutrera et al ., ; see the results of Galiano et al ., ; Kubiak, Galiano & Freitas, ). The greater availability of food is likely a key factor in the choice of habitat, leading species with lower bite forces to inhabit locations with higher soil bulk density.…”
Section: Discussionmentioning
confidence: 98%
“…Species usually use habitats with similar soil characteristics and availability of resources (Lacey et al ., ). However, some species are found in habitats with sharp differences in resource availability and soil characteristics, as is the case for Ctenomys minutus Nehring, 1887 (Galiano, Bernardo‐Silva & Freitas, ; Galiano, Kubiak & Freitas, ; Kubiak, Galiano & Freitas, ; Galiano et al ., ). This species has solitary habits and its distribution is restricted to the coastal plains of southern Brazil, where populations occur along a linear extension of approximately 500 km (Freitas, ; Freygang, Marinho & Freitas, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This species has solitary habits and its distribution is restricted to the coastal plains of southern Brazil, where populations occur along a linear extension of approximately 500 km (Freitas, ; Freygang, Marinho & Freitas, 2004). Along its distribution C. minutus is found in two distinct habitats: sand dunes and sand fields, which have marked differences in habitat characteristics including plant biomass, vegetation cover and soil hardness (see Galiano et al ., ; Kubiak et al ., for details of habitat characteristics for the species in the region) (see Fig. ).…”
Section: Introductionmentioning
confidence: 99%